Comparison of Clinical and Angiographic Profiles of Patients with or without Left Main Coronary Artery Disease in Patients Undergoing Angiography for Acute Coronary Syndrome - Samiullah, Javaid Ur Rehman, Saleemullah, Muhammad Abbas Khan, Gulzar Ali Buriro, Nadeem Hassan Rizvi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: High death rates are seen in cases with heart disease affecting the left major coronary artery. The left main coronary artery has different flow dynamics and pathophysiology than other coronary arteries. It is important to identify the best management options for patients with left main coronary artery disease based on their anatomic pattern. Objective: To compare the clinical and angiographic profiles of patients with or without left main coronary artery disease in patients undergoing angiography for ACS. Methods: An observational cross-sectional study was conducted. Invasive coronary angiography was performed on 985 adult patients diagnosed with coronary artery disease throughout a 6-month study period. The research participants were split into two groups: left main (Group 1) and non-left main (Group 2) following coronary angiography. It was determined whether there were any statistically significant variances between the two groups by comparing their demographics, risk factors, and angiograms. Results: In group 1, the mean age and SD are 54.3±8.4 and in group 2, they are 54.4±11.9. There were 748 men (75.9% of the total) and 236 females (23.9%). Out of the male participants, 630 were assigned to Group 2 (non-LMCA) and 118 were placed in Group 1 (LMCA). All of the females were present in group 2. Left main illness tends to be greater in males, as indicated by the results of the comparison research between the two groups (p=0.046). BMI comparisons across the groups indicated no statistically significant difference (p>0.05). The most common presentation was non-ST elevated ACS, which was significantly related to the LM group (p<0.05). The coronary angiogram of 867 patients showed no left main artery involvement in 88.0% of patients, while the left main in 118 cases was 12.0%. For this research, 985 participants had coronary angiography performed by cardiac catheterization. From the total of 985 patients, 89 (9.0%) were classified as having "normal" or "non-critical" coronary arteries, 227 (23.1%) as having "single vessel disease," 296 (30.0%) as having "double vessel disease," and 374 (38.0%) as having "triple vessel disease." There are 867 individuals (88.0%) with no involvement of the left main artery, and 118 patients (12.0%) having left main disease among the population investigated. Conclusion: Patients with NSTE-ACS, diabetes and LMCA disease were considerably more likely to be men. They were also more likely to have a favorable family history (ACS). Triple vessel disease and distal left main disease were more prevalent among patients. Keywords: Left main coronary artery, Coronary angiography, Coronary artery disease, acute coronary syndrome.